Vigor Benih Kacang Hijau Pada Budidaya Tanpa Olah Tanah Dengan Aplikasi Pupuk Fosfat Dosis Rendah Yang Ditanam Setelah Padi Sawah - Ichwan S. Madauna (Universitas Tadulako, 2007)
Field trial was conducted in the farming area in Parigi Moutong regency. Vigor test was performed in the Seed Technology Laboratory, Agronomy Department Faculty of Agriculture Tadulako University. This trial lasted from 5 February to 16 July 2006. The aim of this trial was to evaluate the effect of non-tillage and the application of low dosage Phosphorus fertilizer in the rice-field following rice sowing on the initial vigor of mung bean seeds produced. This trial used Block Randomized Design in factorial pattern with three replications. Two factors tested, namely non-tillage practices with four levels, namely non-tillage, non-tillage + mulching, non-tillage + glyphosate, and non-tillage + mulching + glyphosate. The second factor was Phosphorus fertilizer with four levels, namely without Phosphorus fertilizer, 1/3 of recommended Phosporous fertilizer dosage (30 kg P2O5/ha); 2/3 of recommended Phosphorus fertilizer dosage (60 kg P2O5/ha); and as of recommended Phosphorus fertilizer dosage (90 kg P2O5/ha). Differences between treatment were determined by using Least Significant Difference test at 5% and 1%. Results of this tial showed that Phosporous fertilizer and non-tillage system did not have interaction. Application of Phosphorus ar recommended dosage had the highest dried-seed yield per hectare, germination (97,50 %) and germination rate (29,457 %)